The impacts of the lack of basic sanitation on the disease process of the Brazilian population: A narrative literature review (Research, Society and Development, 2025)
Basic sanitation is a set of actions aimed at promoting public health and preserving natural resources. In Brazil, the unplanned urbanization process has generated historical deficits that persist, leading to diseases and worsening public health conditions. This study aims to analyze the impact of the lack of basic sanitation on the illness process of the Brazilian population, reflecting on its relationship with diseases and the public policies necessary to implement an intersectoral and inclusive management model. The qualitative research was developed based on articles available in the SciELO and CAPES databases, through thematic analysis. The results indicate that the lack of basic sanitation directly affects the environment and quality of life, requiring intersectoral public policies and structural investments. It is concluded that strengthening sanitation policies and primary health care is essential to improve health and reduce regional inequalities in the country.